FINANCIAL LITERACY OF MICRO, SMALL, AND MEDIUM ENTERPRISES OF CONSUMPTION SECTOR IN PROBOLINGGO CITY - Elok Sri Utami; Mega Rizky Aprilia; Ihrom Caesar Ananta Putra (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2021)
This study aims to describe financial literacy, use of technology and financial behavior with the performance of MSMEs Consumption Sector in Probolinggo City, with 51 MSMEs that have been operating 3 years to become a research sample. Data obtained from questionnaire were used combination of dichotomus and Likert scale to know level of financial literacy among SMEs owner in Probolinggo City, use of technology and financial behavior. The result of this study indicate that a medium level of financial literacy among SMEs owner in Probolinggo City. The MSME owners have not used technology maximally to help business activities. The MSME owners have shown responsibility of financial behavior so it can improve the performance of MSMEs.